'I don't know if I should believe him': Knowledge and believability in interviews with children. (20th February 2013) - Iversen, Clara
<x xml:space="preserve">Abstract</x> Social psychologists interested in social interaction have, in recent years, addressed the ways that people negotiate 'who is entitled to know what' across a variety of conversational settings. Using recordings of interviews conducted as a part of a Swedish national evaluation of interventions for abused children, the current article examines how children navigate knowledge and its moral implications. The analysis focuses on a particular question ('What do you believe [the perpetrator] thinks about what he has done'), which draws on the psychological concept of mentalization: the cognitive ability to picture others' mental states based on their behaviour. The findings suggest that the concept of mentalization fails to account for the moral properties of knowing someone's thoughts: The perpetrator, most often the child's father, must be believable – recognized as both credible and knowable – for the children to claim access to his thoughts. The interviewees used contrastive constructions in claims of (no) access to their fathers' thoughts as they simultaneously contested idiomatic knowledge that undermined their claims. The article contributes to recent developments in discursive social psychology concerning how subjectivity, in particular, epistemic stance, is managed in institutional interaction, and continues the discursive psychological project of respecifying concepts such as mentalization.